2019
DOI: 10.1007/s12257-018-0408-0
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cariogenic Characteristics of Rubusoside

Abstract: Streptococcus mutans plays an important role in the development of dental caries in humans by synthesizing adhesive insoluble glucans from sucrose by mutansucrase activity. To explore the anti-cariogenic characteristics of rubusoside (Ru), a natural sweetener component in Rubus suavissimus S. Lee (Rosaceae), we investigated the inhibitory effect of Ru against the activity of mutansucrase and the growth of Streptococcus mutans. Ru (50 mM) showed 97% inhibitory activity against 0.1 U/mL mutansucrase of S. mutans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…The effect of rubusoside on related proteins is due to the disruption of the spatial conformation of the protein. A recent study suggested that rubusoside may inhibit the mutansucrase activity of S. mutans by influencing hydrophobic and hydrogen bond (H bond) interactions between rubusoside and the amino acid residues at the active-site pocket of mutansucrase (47). More studies of S. mutans are needed, and the quantitative PCR results need to be confirmed at the protein level to verify the current results.…”
Section: Discussionmentioning
confidence: 83%
“…The effect of rubusoside on related proteins is due to the disruption of the spatial conformation of the protein. A recent study suggested that rubusoside may inhibit the mutansucrase activity of S. mutans by influencing hydrophobic and hydrogen bond (H bond) interactions between rubusoside and the amino acid residues at the active-site pocket of mutansucrase (47). More studies of S. mutans are needed, and the quantitative PCR results need to be confirmed at the protein level to verify the current results.…”
Section: Discussionmentioning
confidence: 83%
“…Alternatively, hyaluronic acid can be produced by microbial fermentation using Streptococcus species. For a long time, industrial-scale production of hyaluronic acid has been performed using a pathogen Streptococcus zooepidemicus (Kim et al, 1996; Schiraldi et al, 2010), which produces a pathogenic factor together hyaluronic acid that contributes to forming the extracellular capsule (Kim et al, 2019). Because of this risk, there has been increasing interest in engineering of non-pathogenic microorganisms, including genus of Escherichia, Bacillus, Lactococcus , and Agrobacterium , for hyaluronic acid production (Widner et al, 2005; Chien and Lee, 2007; Mao and Chen, 2007; Yu and Stephanopoulos, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Lengsfeld et al demonstrated that berryderived polysaccharides can combat H. pylori infection in vivo by preventing bacterial binding to the gastric mucosa [53]. Additional studies have shown antibacterial effects for berry-derived sanguiin H-6 [35] and rubusoside [54]. Further experiments are needed to identify the raspberry and blackberry compounds that mediate antimicrobial activity against H. pylori.…”
Section: Discussionmentioning
confidence: 99%